Dynamic Resource Allocation Algorithm Based on Periodic Alternation of Bands in C+L+S-bands EONs - Zhang, Wenchao; Yin, Shan; Liu, Lihao; Chai, Yutong; Huang, Shanguo (2022 Asia Communications and Photonics Conference (ACP), 2022)
We propose a novel dynamic algorithm in the C+L+S-bands network, with flexible resource scheduling by considering the time behavior of traffic and the accumulation of nonlinear interference, which significantly improves the network performance.